Implications of High Temperature and Elevated CO2 on Flowering Time in Plants - Jagadish, S. V. Krishna; Bahuguna, Rajeev N.; Djanaguiraman, Maduraimuthu; Gamuyao, Rico; Prasad, P. V. Vara; Craufurd, Peter Q. (Frontiers in Plant Science, 2016)
Flowering is a crucial determinant for plant reproductive success and seed-set. Increasing temperature and elevated carbon-dioxide (e[CO2]) are key factors of climate change factors that could affect plant fitness and flowering related events. Addressing the effect of these environmental factors on flowering events such as time of day of anthesis (TOA) and flowering time (duration from germination till flowering) is critical to understand the adaptation of plants/crops to changing climateenvironment and hence is the major aim of this review. Increasing ambient temperature is the major climatic factor that advances flowering time in crops and other plants, with a modest effect of e[CO2]. Integrated environmental stimuli such as photoperiod, temperature and e[CO2] regulating flowering time is discussed. The critical role of plant tissue temperature influencing TOA is highlighted and the need for crop models need to substitute ambient air temperature with canopy or floral tissue temperature to improve predictionsis recommended. Increasing ambient temperature is the major climatic factor that advances flowering time in crops and other plants, with a modest effect of e[CO2]. Integrated environmental stimuli such as photoperiod, temperature and e[CO2] regulating flowering time is discussed. A complex signaling network of flowering regulation with change in ambient temperature involving different transcription factors (PIF4, PIF5), flowering suppressors (HvODDSOC2, SVP, FLC) and autonomous pathway (FCA, FVE) genes, mainly from Arabidopsis Arabidopsis, provides a promising avenue tolead in improve our understandinging of the dynamics of flowering time under changing climate. Conversely, e[CO2]-Elevated CO2 mediated changes in tissue sugar status and a direct [CO2]-driven regulatory pathway involving a key flowering gene, MOTHER OF FT AND TFL1 (MFT), are emerging evidence for the role of e[CO2] in flowering time regulation.